2022
DOI: 10.3390/jmse10081110
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Weight Optimization of a Nonlinear Model Predictive Controller Using a Genetic Algorithm for Ship Trajectory Tracking

Abstract: This paper presents a weight optimization method for a nonlinear model predictive controller (NMPC) based on the genetic algorithm (GA) for ship trajectory tracking. The weight coefficients Q and R of the objective function in NMPC are obtained via the real-time optimization of the genetic algorithm instead of the trial and error method, which improves the efficiency and accuracy of the controller. In addition, targeted improvements are made to the internal crossover operator, mutation operator, crossover rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Dunjing Yu et al used GA to optimize the nonlinear predictive controller of the ship trajectory tracking model. The experiments showed that GA improved the efficiency and accuracy of the controller [54].…”
Section: Literature Reviewmentioning
confidence: 98%
“…Dunjing Yu et al used GA to optimize the nonlinear predictive controller of the ship trajectory tracking model. The experiments showed that GA improved the efficiency and accuracy of the controller [54].…”
Section: Literature Reviewmentioning
confidence: 98%
“…Many scholars have also studied the above two problems. Yu et al 22 proposed an improved MPC controller that can dynamically adjust the weight matrix in the objective function according to the reference trajectory curvature so as to improve the tracking accuracy of the trajectory. However, it is difficult to balance multiple constraints of the system by just changing the size of the weight matrix overall rather than adjusting individual weights in the weight matrix according to the trajectory changes.…”
Section: Introductionmentioning
confidence: 99%
“…[18] employed a nonlinear model predictive control (NMPC) model based on an accurate ship motion model to control the trajectory tracking, efficiently improving the anti-disturbance capability. [21] presented a weight optimization method for a nonlinear MPC (NMPC) based on the genetic algorithm (GA) for ship trajectory tracking. [7] used the model predictive control (MPC) method under constraints to track planned trajectories and optimize motion processes, while ensuring control stability through Lyapunov's theorem.…”
Section: Introductionmentioning
confidence: 99%